Selected linguistic aspects of content designers’ posts (on Coca-Cola brand example) - Ozga, Krzysztof (Papers in Linguistics, 2019)
The paper is an attempt to linguistically describe the most important features of the language of contemporary online advertising. The aim of the article is to present and analyze the changes in language caused by modern forms of communication in context of contemporary content marketing strategies on social media sites. The author based the research on a selection of language aspects of posts appearing on Facebook and on the Coca-Cola fan page. The characteristics of the linguistic properties adopted for the study concern three research areas: lexis, grammar (with particular emphasis on syntax) and textual phenomena.